A COMPARATIVE STUDY OF DIRECT AND INDIRECT TAX REFORMS IN INDIA - Pillai, Seema (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study presents a comparative analysis of direct and indirect tax reforms in India over the past few decades. The research examines the evolution, impact, and effectiveness of these reforms in shaping India’s economic landscape. By exploring key policies, challenges, and outcomes associated with both tax systems, the study provides insights into how tax reforms have influenced economic growth, revenue generation, and fiscal policies. The comparative approach aims to assess the strengths and weaknesses of direct and indirect taxation in fostering economic development, equity, and administrative efficiency. This comprehensive analysis contributes to a deeper understanding of the dynamics of tax reform in India and its broader implications for the economy.